EVALUASI PENERAPAN PEMBELAJARAN BERBASIS STEAM ( SCIENCE, TECHNOLOGY, ENGINEERING, ARTS, MATHEMATICS) DALAM MENGEMBANGKAN KREATIVITAS PADA ANAK DI TK LENTERA DESA LUNJUK KABUPATEN SELUMA - Deri Sukma Wijayanti; Asniti Karni; Fidhia Andani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the importance of developing early childhood creativity through innovative, child-centered learning. One approach that can be used to develop children's creativity is STEAM-based learning (Science, Technology, Engineering, Arts, and Mathematics). Therefore, this study aims to determine the extent to which STEAM-based learning is implemented in developing children's creativity at Lentera Kindergarten, Lunjuk Village, Seluma Regency. This study uses a descriptive quantitative approach. The research subjects consisted of the principal, treasurer, secretary, and class teachers, totaling four respondents. Data collection techniques used observation, questionnaires, and documentation. The research instrument was a questionnaire consisting of 25 statements. The data analysis technique used was percentage. Based on the results of the research conducted on the evaluation of the application of STEAM-based learning in developing children's creativity at Lentera Kindergarten, Lunjuk Village, Seluma Regency, the results of the questionnaire were obtained. The researcher administered 25 questions to the principal, treasurer, secretary, and class teachers. The distribution of the scores was found to range from a lowest score of 64 to a highest score of 90. The results across all questionnaires were categorized as very good (25%), good (50%), sufficient (25%), and poor (0%). Therefore, the evaluation of the application of STEAM-based learning in developing children's creativity at Lentera Kindergarten, Lunjuk Village, Seluma Regency can be understood to have been implemented successfully.